Classroom Cybersecurity Lab Platform: A Self-Hosted Private Cloud Approach for Practical ICT Education - Roslan, Abdullah Saniy (Tropical Scientific Journal, 2026)
Objective: To design, develop, and evaluate a self-hosted private cloud platform—the Classroom Cybersecurity Lab Platform—to overcome the limitations of traditional labs and enhance the practical ICT education at Politeknik Mersing. The aim is to provide a scalable, cost-effective, and fully controlled environment for hands-on training in Capture-the-Flag (CTF), Ethical Hacking, and Malware Analysis. Research Method: The study employed a Design Science Research (DSR) methodology. This consisted of four phases: requirements analysis, 3-layer system architecture design (integrating Moodle and Proxmox), prototype implementation (including the custom Moodle-Proxmox integration plugin), and a two-part evaluation plan. Findings: Experimental deployment demonstrated the platform's feasibility in reducing reliance on commercial subscriptions and enhancing student engagement. The design successfully shifts the computational load from student hardware to a central server and confirms that self-hosted lab platforms can address institutional autonomy, curriculum relevance, and equity of access in cybersecurity education. Originality: This research introduces a novel, self-hosted private cloud solution that tightly and seamlessly integrates the Moodle Learning Management System (LMS) with the Proxmox Virtual Environment (VE) hypervisor via a custom-developed plugin. This holistic approach closes the gap left by other models, providing full pedagogical control and cost-free, high-performance lab access to all diploma-level students